Informality and the Infrastructures of Inclusion: An Introduction. Issue 4 (21st July 2021) - Meagher, Kate
ABSTRACT: The worrying welfare and political risks of expanding informal economies have put concerns about economic inclusion at the heart of contemporary development thinking — concerns further intensified in the wake of the COVID‐19 pandemic. Amid a collective 'will to include', this Debate adopts an infrastructural lens to decipher the distributive and governance implications of the complex institutional, financial and digital linkages through which informal workers and consumers are being included in the circuits of contemporary market economies. Looking beyond imaginaries of seamless linkages, the articles in this Debate examine the specific processes through which these inclusive connections engage with informal actors, focusing on how they work and for whom. Articles focus on various types of inclusive infrastructures that connect deprived communities to jobs, resources and social citizenship, ranging from social protection systems to employment linkages and services for hard‐to‐reach populations. With a view to cutting through the ideological blurring of inclusive discourses, this Introduction will examine the strategies of legibility and regulatory restructuring effected through inclusive infrastructures. It reveals the hidden politics of inclusive linkages, reflects on the techniques of governance operating through socio‐technical connections, and examines processes of resistance and failed connections reworking inclusive infrastructures from below.